KONTSRUKSI SOSIAL PADA MALE ENTITLEMENT DALAM BUKU KIM JI YEONG BORN IN 1982 - Alyssa Naura Azzahra; Muhammad Taufik; Shabrina Salsabila; Ikhsan Nur Gakuba; Pia Khoirotun Nisa (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to understand how social constructs can shape the attitude of Male Entitlement within society. With the increasing behavior that tends to prioritize one gender, namely men, this paper seeks to further explore the relationship between social constructs and Male Entitlement itself. The author uses Cho Nam Joo's book, Kim Ji-Yeong Born in 1982, as the research object to understand how the social constructs in the background of the book can encourage Male Entitlement attitudes in the surrounding community. This research is conducted through a literature study using various books, journals, and articles that support the theme and title of the study. Through this research, the author gains perspective on the relationship between social constructs and Male Entitlement and also understands how Male Entitlement in the book Kim Ji-Yeong Born in 1982 is practiced by society through existing social constructs.